Pedagogical communication in early childhood education practice: Factors shaping future teachers’ interaction skills with 5-6-year-old preschool children - Kim, Yen Tran Thi; Thuy, Hoan Vu (Edelweiss Applied Science and Technology, 2026)
Communication skills with preschool children play a crucial role in creating a safe educational environment and promoting the holistic development of young children. This study aims to explore the factors determining the communication skills of future preschool teachers during their internship by integrating individual psychological factors and school support mechanisms within a unified analytical framework. Using a quantitative research method, data were collected from 311 preschool education students from four universities in Vietnam. The results show that knowledge of child psychology, preschool teacher training programs at universities, internship environment and conditions, and self-confidence all have a positive and significant influence on communication skills during internships. In this study, self-confidence emerged as the strongest predictor (β = 0.299, t = 6.301), highlighting the central role of the individual in shaping the communication performance of future teachers in a practical setting. The research results provide useful evidence suggesting that universities training early childhood education students should adjust their curricula and practices to focus on effective communication skills before they enter the future job market.